2018
DOI: 10.1021/acs.jafc.8b02151
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Methyl (5Z)-[2-(2,4,5-Trioxopyrrolidin-3-ylidene)-4-oxo-1,3-thiazolidin-5-ylidene]acetates as Antifungal Agents against Potato Diseases

Abstract: Synthesis, isomerism, and fungicidal activity against potato diseases of new (5 Z)-[2-(2,4,5-trioxopyrrolidin-3-ylidene)-4-oxo-1,3-thiazolidin-5-ylidene]acetate derivatives with 1,3-thiazolidine-4-one and pyrrolidine-2,3,5-trione moieties linked by an exocyclic C═C bond were described. Their structures were clearly confirmed by spectroscopic and spectrometric data (Fourier transform infrared spectroscopy, H andC nuclear magnetic resonance, and mass spectrometry), elemental analysis, and X-ray diffraction cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…In their work, they found that almost all synthesized compounds showed fungicidal activity and, specifically derivatives 151-153 exhibited a concentrationdependent activity on C. albicans biofilm (Figure 15). On the other hand, Obydennov et al 74 In the preparation of 2,4,5-pyrrolidinetrione core structures 154-159, Obydennov et al 74 followed a straightforward synthetic protocol using enamides and oxalyl chloride as starting materials. In their route, Obydennov et al 74 Malaria has killed hundreds of thousands people every year.…”
Section: Mementioning
confidence: 99%
“…In their work, they found that almost all synthesized compounds showed fungicidal activity and, specifically derivatives 151-153 exhibited a concentrationdependent activity on C. albicans biofilm (Figure 15). On the other hand, Obydennov et al 74 In the preparation of 2,4,5-pyrrolidinetrione core structures 154-159, Obydennov et al 74 followed a straightforward synthetic protocol using enamides and oxalyl chloride as starting materials. In their route, Obydennov et al 74 Malaria has killed hundreds of thousands people every year.…”
Section: Mementioning
confidence: 99%
“…At present, the common antimicrobial agents against potato diseases are a variety of synthetic fungicides, which in addition to being beneficial, also have adverse effects on the host and the environment, resulting in pathogen resistance to the fungicides. [8][9][10] Therefore, new and effective natural fungicides are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…e traditional commercial fungicides and insecticides used to prevent and control plant diseases could increase the yield, improve the quality of agricultural products, and also not reduced huge loss annually [5,6]. However, the misuse of traditional fungicides and insecticides had speeded up the resistance of plant diseases, which is rapidly becoming a huge challenge in agriculture [7,8]. erefore, it is still an urgent and meaningful task to develop the novel, highly efficient, and promising pesticides.…”
Section: Introductionmentioning
confidence: 99%